“Get Haircut” Application based on Mobile Android Using React Native Framework - Nur Alamsyah; Wala Erpurini; Wia Handayani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Salon or Barbershop is one of the businesses that engaged in services. At this time, hair care is one of the appearance factors that are often considered by both men and women. This is further strengthened by the increase in the salon or barbershop business in Cirebon. Every time the number of customers at the salon or barbershop is increasing and of course it creates problems, such as, regarding reservations (Booking) and also incoming transaction reports. From these problems, we need a system that can handle these problems. Get Haircut Application is an android-based application built using the React Native framework with the PHP programming language that can make it easier for salons or barbershops to receive orders from customers online. In addition, this application is able to process queue number data, service data and related data. This application is made using the Rational Unified Process (RUP) development method.